Futuros en pugna protagonismos, dinámicas y sentidos durante el tercer gobierno peronista (1973-1976) - Cernadas, Jorge; Lenci, Laura (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2021)
Futures in conflict: Protagonism, dynamics and meaning during the third Peronist government (1973 - 1976): A crowd of people changing the dynamics and the meaning of the presidential inauguration. Another one surrounding Villa Devoto prison to "free" the political prisoners in it. A third crowd, in República de los Niños, calling for the democratization and social management of the premises. A project for university that is beyond the policies of Peronism and beyond those of the government itself, with which it identifies. A minister dispensing with official cars; another one promoting the enactment of a new foreign investment law that limits transnational capital. Grassroots labor activists raising their voices and exercising democracy beyond the limits of representativeness. One branch of the "traditional left" having difficulties in providing answers in a climate that defies its political parameters. These are images of an Argentina that seemed to have another possible future, which would nevertheless end up submerged in the maelstrom of state terrorism. This book is the result of research and debate on the third Peronist government (1973-1976), carried out by researcher professors from the national universities of La Plata, General Sarmiento, La Pampa and Buenos Aires, brought together into peer discussion. The aim was to broaden the knowledge about this historical period so seldom addressed, and to revisit politics as a central dimension in order to understand the intensity of that past and to return its historical and necessarily relational, situated and dynamic character.
Keywords: Geschichte 1973-1976; Peronismus; Argentinien; Peronist government; Argentina; Political history; Aufsatzsammlung